Deciphering the Active Compounds and Mechanisms of HSBDF for Treating ALI via Integrating Chemical Bioinformatics Analysis - Wang, Yanru; Jin, Xiaojie; Fan, Qin; Li, Chenghao; Zhang, Min; Wang, Yongfeng; Wu, Qingfeng; Li, Jiawei; Liu, Xiuzhu; Wang, Siyu; Wang, Yu; Li, Ling; et al. (Frontiers in Pharmacology, 2022)
Huashi Baidu Formula (HSBDF)has a remarkable clinical efficacy in treating acute lung injury (ALI).It has been officially approved by the National Medical Products Administration of China for drug clinical trials. Nevertheless, the regulated mechanisms of HSBDF and its active compounds in Plasma to against ALI were rarely studied. Based on these considerations, the key anti-inflammatory compounds of HSBDF were screened by molecular docking and binding free energy. Key compounds were further identified whether were in plasma by LC/MS. Network pharmacology was employed to identify the potential regulation mechanism of key compounds in plasma. Next, the network pharmacological prediction was validated by a series of experimental assays, including CCK8, EdU staining, test of TNF-α, IL-6, MDA, T-SOD and Flow cytometry to identify active compounds. Molecular dynamic simulation and bindng interaction pattern were used to evaluate the stability and affinity between active compounds and target. Finally, the active compounds were subjected to predictions pharmacokinetic properties. Molecular docking revealed that HSBDF had potential effects of inhibiting inflammation by acting on IL-6R and TNF-α. Piceatannol, emodin, aloe-emodin, rhein, physcion, luteolin and quercetin were key compounds may to ameliorate ALI, and among which, there were 5 compounds (emodin, aloe-emodin, rhein, luteolin and quercetin) in plasma. Network pharmacology results suggested that five key compounds in plasma likely inhibited ALI by regulating inflammation and oxidative damage. Test in vitro suggested that HSBDF (0.03125mg/mL), quercetin (1.5625μM), emodin (3.125μM), rhein (1.5625μM) have the function of anti-inflammatory and against oxidative damage and decrease apoptosisin in a flammation environment by LPS-stimulated. What’s more, active compounds (quercetin, emodin, rhein) had good development prospect, fine affinity and stable conformations with target protein. In summary, this study suggested that HSBDF and its key active components in plasma (quercetin, emodin, rhein) can decrease levels of pro-inflammatory factors (IL-6 and TNF-α), decrease expression of MDA, increase expression of T-SOD and decrease cell apoptosis in an inflammation environment. These data suggest that HSBDF has significant effect on anti-inflammation, anti-oxidative stress and also can decrease cell apoptosis in treating ALI. These findings provided an important strategy for developing new agents and facilitated clinical use of HSBDF against ALI.